Reproductive state influences the degree of risk tolerance for a seasonally breeding mesopredator. (21st April 2021) - Marneweck, Courtney J; van Schalkwyk, O Louis; Marneweck, David G; Beverley, Grant; Davies-Mostert, Harriet T; Parker, Daniel M
Abstract: The risk of predation can alter the way animals perceive costs and benefits in their environment, on which foraging decisions are made. To maximize fitness, animals with offspring show the most pronounced alteration in behavior because mothers experience increased nutritional requirements and increased vulnerability to predation. Therefore, the tolerance of risk is shaped, in part, by reproductive state. Like prey species, mesopredators balance a trade-off between food and predation to maximize fitness. However, few studies have acknowledged its importance. We investigated how mesopredators may alter their space use between periods when young are and are not vulnerable. Investigating the fine-scale space use of 19 packs of African wild dogs Lycaon pictus in the Kruger National Park, we found lower risk tolerance of denning packs; they re-visited area less frequently as lion and impala density increased and thus reduced the likelihood of risky encounters by avoiding areas where both risk and reward were high. By contrast, non-denning packs re-visited area less frequently as lion density increased and impala density decreased and thus avoided areas where reward was low, especially if risk was high. These results suggest that wild dogs shift their patterns of space use when the pack is most vulnerable. Ultimately, we found evidence of decreased risk tolerance by denning packs, likely because of increased vulnerability of lactating mothers and immobile pups. More broadly, our findings suggest that risk tolerance is dependent on reproductive state for mesopredators and should be considered as a possible mechanism for other mesopredators as well. Abstract : Predators are scared of predation too. African wild dogs, a mesopredator, alter their space use when they are more vulnerable to avoid contact with the apex, lions. While denning, wild dogs infrequently visit areas of both higher impala and higher lion density and spend longer visits in areas of low impala density further from their den. Like herbivores, mesopredators with young must also avoid risk of predation, and the tolerance of this risk shifts with reproductive state.